A new species of Mollinedia (Monimiaceae, Laurales) from the Quadrilátero Ferrífero, Brazil - Zavatin, Danilo Alvarenga; Ramos, Renato; Watanabe, Mauricio Takashi Coutinho; Pedrosa, Luciano Gonçalves; de Lírio, Elton John (PhytoKeys, 2023)
Monimiaceae comprises approximately 26 genera and 250 species, with a pantropical distribution, predominantly occurring in humid forests. In Brazil, it is represented by five genera and 47 species, most of which are found in the Atlantic Forest, particularly in dense ombrophilous forest. Nevertheless, studies on this family in other biomes and vegetation types in Brazil are still scarce. The Quadrilátero Ferrífero (QF), a region located in the state of Minas Gerais, exhibits high plant species richness and endemism. During collections and analysis of herbarium materials from this region, some specimens of Mollinedia caught our attention due to a combination of characteristics that do not match those of any described species within the genus. For this reason, we describe this new taxon and assess its risk of extinction. Additionally, we review the occurrences of Monimiaceae in the QF and provide maps of its geographical distribution. With the description of this new species, the region now hosts eight species of Monimiaceae, two from the genus Macropeplus and six from Mollinedia . The new species is the first endemic species of the Monimiaceae family to be described in the QF. Concerning the extinction risk assessment, the new species was assessed as critically endangered.